ANALISIS EFISIENSI TEKNIS PERBANKAN DI INDONESIA - Kartika Dewi; Rahmat Siauwijaya (Jurnal Manajemen, 2016)
This research investigates the technical eficiency of the banks listed in Jakarta Stock Exchange inIndonesia from year 2009 to 2012. This research also compares the levels of technical efficiency betweenBank Umum Milik Negara (BUMN), Bank Umum Swasta Nasional (BUSN) Devisa and Bank UmumSwasta Nasional (BUSN) Non Devisa by using non-parametric Data Envelopment Analysis (DEA).DEA was calculated using input orientation and variable return to scale. ANOVA is also applied tocompare efficiency between banks. The sample was selected using purposive sampling of 33 banks listed inJakarta Stock Exchange for period 2009-2012. The result of this study shows that BUMN is the mostefficient banks compared to the BUSN Devisa and BUSN Non Devisa. Furthemore, BUSN devisa is theleast efficient bank. Finally, this research found that there is a significant difference of the technicalefficiency between the groups of banks.